Evaluación de uso de la energía eléctrica en la curtiembre PROMEPELL S.A. Del cantón Ambato. Período 2012-2013. Propuesta de un programa para el uso eficiente de la energía eléctrica en la planta de producción. - Mayorga Pérez, Oswaldo Efraín (2014)
In today´s open and globalized economy, service development in industry calls for the reduction of costs and to maximize competitiveness. In the context of industry, electrical energy supply is a critical part of the productive process, and inefficiency can prove costly. Lack of knowledge of these inefficiencies at the plant of CURTIEMBRE POMEPELL S.A. in Ambato Canton currently results in high energy bills. Therefore, the objective of this study is to evaluate the causes of this inefficiency and to create a program to reduce the monthly energy bill. The purpose is to determine methods to better use electrical energy, without reducing the services that it provides. This study consisted of a literature review and field research with diagnostic and explicative levels which allowed diagnosis of the current situation and determination of the strategic options for the efficient use of the electrical energy. Among the most profitable opportunities within the program are: control or administration of the maximum demand, potency factor, energy consumption, the use of more efficient machines, and the automation of processes. The implementation of the proposals will reduce 24% of the energy consumption bill, increasing the economic efficiency of the plant and guaranteeing its profitability in internal and external markets